A survey on mobile WiMAX. - Bo Li (IEEE Communications magazine)
The IEEE 802.16 standard, commonly known as WiMAX, is the latest technology that has promised to offer broadband wireless access over long distance. Since 2001 WiMAX has evolved from 802.16 to 802.16d for fixed wireless access, and to the new IEEE 802.16e standard with mobility support. In this article we provide an overview of the state-of-the-art mobile WiMAX technology and its development. We focus our discussion on QoS provisioning and mobile WiMAX specification.